EXPLORING KURDISH EFL STUDENTS’ VIEWS ON THE ASSESSMENT PROCESS AT UNIVERSITY LEVEL - Murad, Ivan; Malo , Sanan (Humanities Journal of University of Zakho, 2025)
The current study aims to investigate Kurdish EFL students’ views of the assessment process conducted at EFL departments of public universities in the Kurdistan Region of Iraq (KRI). Due to the fact that assessment is the core factor for students’ learning, involvement, and evaluation as the only gauge for their progress and development, much attention needs to be given to the assessment process. This study specifically aims at studying the perceptions of the Kurdish EFL students of the criteria including design, administration, purpose, effectiveness and washback, scoring and grading, and feedback of testing and assessment process. Hence, for the purpose of data collection, a questionnaire was administered to 116 students of semesters 3,5, and 7 at the English language departments of some public universities in the KRI during the academic year 2024-2025. Cronbach Alpha was used to analyze the reliability of the items of the questionnaire along with SPSS (version 25) to analyze the mean values of the items and ANOVA was utilized to compare the mean values across the six criteria. Findings indicate significant challenges in the alignment and execution of testing and assessment processes in higher education. While testing and assessment items align with course objectives, they often fail to adequately measure critical thinking and comprehensive language skills. Procedural issues, including unclear instructions, unfair scoring and grading practices, and overemphasis on grading rather than fostering students’ progress and engagement, have badly affected the effectiveness of assessments. Additionally, environmental factors such as cheating, unsupportive classroom dynamics, and poor seating quality negatively impact students' performance. A lack of constructive feedback further hinders the development of students’ overall skills and learning outcomes. The findings further highlight the need for a holistic approach to assessment that emphasizes student growth, fair evaluation, and the integration of diverse language competencies.